2019
DOI: 10.1002/adfm.201906763
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Open‐Circuit Voltage Enhancements in Planar Perovskite Solar Cells Induced by Addition of Bulky Organic Cations

Abstract: The origin of performance enhancements in p‐i‐n perovskite solar cells (PSCs) when incorporating low concentrations of the bulky cation 1‐naphthylmethylamine (NMA) are discussed. A 0.25 vol % addition of NMA increases the open circuit voltage (Voc) of methylammonium lead iodide (MAPbI3) PSCs from 1.06 to 1.16 V and their power conversion efficiency (PCE) from 18.7% to 20.1%. X‐ray photoelectron spectroscopy and low energy ion scattering data show NMA is located at grain surfaces, not the bulk. Scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…The increased Fermi level near the surface of perovskites should benefit from the passivated hole traps at crystal boundaries and would facilitate the efficient holes transport in the devices. [ 39–41 ] Furthermore, the existence of Crown on the surface of perovskite films would well reduce the surface hydrophilicity of FACsPbI 3 perovskite films consistent with the previously reported work, [ 31 ] and also verified by the enlarged water contact angle of 76.8° compared with 65.8° in bare FACsPbI 3 film in a short time (Figure 3f; Video S1, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…The increased Fermi level near the surface of perovskites should benefit from the passivated hole traps at crystal boundaries and would facilitate the efficient holes transport in the devices. [ 39–41 ] Furthermore, the existence of Crown on the surface of perovskite films would well reduce the surface hydrophilicity of FACsPbI 3 perovskite films consistent with the previously reported work, [ 31 ] and also verified by the enlarged water contact angle of 76.8° compared with 65.8° in bare FACsPbI 3 film in a short time (Figure 3f; Video S1, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…Consequently, the shifts in both W f,air and valence band of P2 films indicate the surface‐anchored PMAI dipoles could significantly change the surface states of perovskite films. [ 47,48 ]…”
Section: Figurementioning
confidence: 99%
“…Currently, the most commonly used perovskite is MAPbI 3 and PSCs using this absorber can now achieve over 20% in PCE. [15,[121][122][123] However, as discussed in Section 2, the hygroscopic nature and high temperature vulnerability of MAPbI 3 makes it more difficult to prepare in ambient conditions and thus making scale up for commercialization unlikely. [84] For example, it was reported that MAPbI 3 undergoes a phase transition between ordered tetragonal and disordered cubic structure at around 57 °C.…”
Section: Composition Engineeringmentioning
confidence: 99%
“…Although the poly(triaryl amine)-based polymers are air stable, [291][292][293] have favorably high water-contact angels, [290] and can produce high efficiency PSCs, [36,123] their complex synthesis and high cost is still a limiting factor. In contrast, nickel oxide (NiO) is an alternative HTM which retains high chemical stability, hole mobility, low cost, and is simple to synthesize.…”
Section: Hole Transport Layermentioning
confidence: 99%